Analysis of Health Product Communication Strategy by Company XYZ in Fulfilling the Code of Conduct in the Pharmaceutical Industry - Ferdy Senjatiana; Mochammad Kresna Noer (CV. Publikasi Indonesia, 2025)
The growth of digital startups in Indonesia faces major challenges, including limited access to funding, low digital literacy, and uneven infrastructure, which hinder business sustainability. PT Telekomunikasi Selular (Telkomsel), through its CSR program